Development of an experimental model for vascularized adrenal gland transplantation in rats - Ozcan, Cumhur; Hazinedaroglu, Selcuk Mevlut; Tug, Tugbay (Frontiers in Surgery, 2026)
AimThe adrenal gland is a vital endocrine organ responsible for maintaining physiological homeostasis. Bilateral adrenalectomy results in adrenal insufficiency, requiring lifelong hormone replacement therapy. This study aimed to establish a reproducible experimental model for vascularized adrenal gland transplantation in rats.Materials and methodsTwenty male Wistar Albino rats (180–220 g) were randomly assigned into two equal groups (n = 10 each): control and transplantation. The control group underwent bilateral total adrenalectomy. In the transplantation group, vascularized adrenal grafts—including the adrenal artery and vein with attached aortic and inferior vena cava segments—were anastomosed end-to-side to the recipient's femoral artery and vein using 10-0 nylon sutures under general anesthesia. On postoperative day 15, all recipients underwent bilateral adrenalectomy. On day 100, animals were sacrificed for macroscopic and histopathological evaluation of graft viability.ResultsAll control rats died within 15 days, whereas all transplanted rats survived throughout the 100-day observation period. Macroscopic inspection revealed viable grafts without vascular compromise. Histopathological analysis demonstrated preserved cortical and medullary architecture, confirming the long-term viability of the transplanted adrenal glands.ConclusionThis study presents a technically feasible and reproducible model for vascularized adrenal gland transplantation in rats. The model provides a reliable experimental platform for future research on adrenal physiology and transplantation surgery.